Maternal metabolism affects endometrial expression of oxidative stress and FOXL2 genes in cattle - Gareth Healey (PLOS ONE, 2017)
Intensive selection for milk production has led to reduced reproductive efficiency in high-producing dairy cattle. The impact of intensive milk production on oocyte quality as well as early embryo development has been established but few analyses have addressed this question at the initiation of implantation, a critical milestone ensuring a successful pregnancy and normal post-natal development. Our study aimed to determine if contrasted maternal metabolism affects the previously described sensory properties of the endometrium to the conceptus in cattle. Following embryo transfer at Day 7 post-oestrus, endometrial caruncular (CAR) and intercaruncular (ICAR) areas were collected at Day 19 from primiparous postpartum Holstein-Friesian cows that were dried-off immediately after parturition (i.e., never milked; DRY) or milked twice daily (LACT). Gene quantification indicated no significant impact of lactation on endometrial expression of transcripts previously reported as conceptus-regulated (PLET1, PTGS2, SOCS6) and interferon-tau stimulated (RSAD2, SOCS1, SOCS3, STAT1) factors or known as female hormone-regulated genes (FOXL2, SCARA5, PTGS2). Compared with LACT cows, DRY cows exhibited mRNA levels with increased expression for FOXL2 transcription factor and decreased expression for oxidative stress-related genes (CAT, SOD1, SOD2). In vivo and in vitro experiments highlighted that neither interferon-tau nor FOXL2 were involved in transcriptional regulation of CAT, SOD1 and SOD2. In addition, our data showed that variations in maternal metabolism had a higher impact on gene expression in ICAR areas. Collectively, our findings prompt the need to fully understand the extent to which modifications in endometrial physiology drive the trajectory of conceptus development from implantation onwards when maternal metabolism is altered.